2022
DOI: 10.3389/fphar.2022.768743
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of ADARB1 Facilitates Temozolomide Chemoresistance and Immune Infiltration in Glioblastoma

Abstract: Chemoresistance, especially temozolomide (TMZ) resistance, is a major clinical challenge in the treatment of glioblastoma (GBM). Exploring the mechanisms of TMZ resistance could help us identify effective therapies. Adenosine deaminases acting on RNA (ADARs) are very important in RNA modification through regulating the A-to-I RNA editing. Recent studies have shown that ADARs regulate multiple neurotransmitter receptors, which have been linked with the occurrence and progress of GBM. Here, data from several bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…It reported that RNA modification regulator adenosine deaminases acting on RNA (ADARs) promote TMZ resistance by upregulating p-Akt. U343 expressing low ADARB1 may restore TMZ sensitivity in GB cells by decreased p-Akt [ 45 ]. To study whether the status of PTEN and/or Akt signaling affects the sensitivity of TMZ, we first analyzed the publicly available dataset in the Genomics of Drug Sensitivity in Cancer (GDSC) and The Cancer Genome Atlas Program (TCGA-GB) where GB samples were classified into two groups according to status of PTEN: wild type ( n = 16 in GDSC-GB and n = 102 in TCGA-GB) and mutant ( n = 17 in GDSC-GB and n = 47 in TCGA-GB).…”
Section: Resultsmentioning
confidence: 99%
“…It reported that RNA modification regulator adenosine deaminases acting on RNA (ADARs) promote TMZ resistance by upregulating p-Akt. U343 expressing low ADARB1 may restore TMZ sensitivity in GB cells by decreased p-Akt [ 45 ]. To study whether the status of PTEN and/or Akt signaling affects the sensitivity of TMZ, we first analyzed the publicly available dataset in the Genomics of Drug Sensitivity in Cancer (GDSC) and The Cancer Genome Atlas Program (TCGA-GB) where GB samples were classified into two groups according to status of PTEN: wild type ( n = 16 in GDSC-GB and n = 102 in TCGA-GB) and mutant ( n = 17 in GDSC-GB and n = 47 in TCGA-GB).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, two TMZ-resistant GBM cell lines (T98G-R and U118-R) were established and cultured ( Yan et al, 2019 ; Lu et al, 2022 ). Small interfering RNAs (siRNAs) targeting FANCD2 were purchased from Genepharma (Suzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the forward and reverse primers are provided in Supplementary Table S1 . The relative expression levels were examined using the 2-ΔΔCT method, as shown in previous reports ( Lu et al, 2022 ), and all the detection-related processes were performed at least three times.…”
Section: Methodsmentioning
confidence: 99%